Foreign direct investment, competition and industry performance - Jürgen Bitzer; Holger Görg (Kiel Institute for the World Economy (IfW), 2008)
This paper investigates the productivity effects of inward and outward foreign direct investment using industry and country level data for 17 OECD countries over the period 1973 to 2001. Controlling for national and international knowledge spillovers we argue that effects of FDI work through direct compositional effects as well as changing competition in the host country. Our results show that there are, on average, productivity benefits from inward FDI, although we can identify a number of countries which, on aggregate, do not appear to benefit in terms of productivity. On the other hand, a country's stock of outward FDI is, on average, negatively related to productivity. however, again there is substantial heterogeneity in the effect across OECD countries.
Keywords: F23; 330; Inward FDI; Outward FDI; Productivity; Competition; Foreign direct investment; Direktinvestition; Wissenstransfer; Produktivität; Industrie; Internationaler Wettbewerb; OECD-Staaten